The Obstacles and Problems Facing Building and Designing Modern Cities - Ali day , Jomaa (Journal of College of Education, 2021)
The research tries to diagnose the problems or obstacles that face the design of modern cities in the world and it includes some examples of many Arab countries& other countries in the world through follow-up those problems and diagnosing them and then how to treat them through scientific planned ways regarding constructing and developing the cities and increasing ,showing the importance of those cities by paying attention of human life who live in those cities, modern welfare life away of obstacles and providing the suitable circumstances for human through the daily life type and the living standard, providing suitable housing for the whole city inhabitants equally in all world cities with existence of challenges m n and differences .It is important to find a suitable environment for human living and throw away problems&obstacles which stand in front of the developing and expanding the cities ,rworking to find solutions for them for the sake of all and rise cities especially the Arab Citiesand rising their service, standard, taking care of architectural heritage ,encouraging continuation in the umbra development and international progress,keeping the environment health and taking care of planting trees& green zones,open area and beatification of cities,taking care of architectural heritage in all Arab Cities and other cities in the world regarding their ancient historical heritage and increasing the importance of making modern plans& designs that service all cities and don’t make problems for them ,but contrary providing suitable circumstances for the cities inhabitants,make solutions to treat all problems according to characterstic of every city and its course,and continuation of its existence for the city. The project of the modern city which adhere to the fullest of principles of Athens agreement which one of them states organizing the city and dividing it to four areas depending on its course: housing,work,rest or free time& transportation.